MICHAEL PSELLOS AND IOANE PETRITSI ON INTELLECT - ALEXIDZE, Lela (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2021)
Michael Psellos exposed his theory on intellect in two major texts: De omnifaria doctrina and Philosophica minora. Psellos’ theory is based on different philosophical sources, including, first and foremost, Proclus’ texts. The younger contemporary of Psellos, Georgian philosopher Ioane Petritsi, who was trained in Byzantine philosophical school and was well acquainted with ancient Greek philosophical tradition, also commented on Proclus and his theory of intellect. For Proclus, Psellos and Petritsi intellect is an important entity because it embraces Forms and is, therefore, a basis for all kinds of beings. The aim of this paper is to analyze Psellos’ and Petritsi’s theories of intellect and their interrelationship taking into consideration their dependence on the common philosophical sources, mainly Proclus’ Elements of theology.